(Dis)integration in Global Resource Governance: Extractivism, Human Rights, and Investment Treaties. (24th July 2020) - Cotula, Lorenzo
Abstract: As global material consumption rests on the large-scale production of commodities for food, energy, and raw materials, the governance of natural resources—from national legislation to international trade, investment, and human rights law—has long provided policy arenas for deepening economic integration. Concerns about 'resource nationalism' and critiques of investor–state dispute settlement have raised questions as to whether the world might be entering a phase of economic dis-integration. To problematize linear accounts of (dis)integration, this article explores the legal arrangements that integrate resource-dependent countries into the global economy. It argues that natural resource extraction is facilitated by a legal regime that sustains dis-integration patterns in global resource governance—including relations between state-based and traditional governance systems; between extractive enclaves and national territories; and between different spheres of international regulation. Some of the recent contestation, then, reflects efforts to (re)integrate dis-integrated legal and social realities, by more fully recognizing local systems of practice and belief and more effectively considering human rights in investment processes.